2022
DOI: 10.1002/csr.2256
|View full text |Cite
|
Sign up to set email alerts
|

Embedding sustainability in risk management: The impact of environmental, social, and governance ratings on corporate financial risk

Abstract: This study investigates the effect of corporate social and environmental evaluation on investors' risk perception to explore the potential market risk for public companies that adopt a sustainable and responsible corporate strategy. We referred to the triple corporate assessment according to environmental, social, and governance (ESG) criteria to check whether ESG factors-meant to direct firms toward social and environmental needs-improve corporate market performance or trigger, among investors, a perception o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 106 publications
(200 reference statements)
0
26
0
1
Order By: Relevance
“…Non-financial reporting and ESG are considered fundamental to foster the transition to a sustainable global economy as they combine long-term profitability with environmental protection and social justice (Landi et al, 2022). Whether or not companies decide to incorporate it into their business model may influence, i.e.…”
Section: Non-financial Information Directive Esg and Their Impact On ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Non-financial reporting and ESG are considered fundamental to foster the transition to a sustainable global economy as they combine long-term profitability with environmental protection and social justice (Landi et al, 2022). Whether or not companies decide to incorporate it into their business model may influence, i.e.…”
Section: Non-financial Information Directive Esg and Their Impact On ...mentioning
confidence: 99%
“…It promotes the principles of sustainable development in the business environment. Nevertheless, due to growing environmental challenges, like for instance the climate crisis, CSR proved not to be effective enough (Landi et al, 2022). It was also observed that some enterprises, instead of making real use of its potential to stimulate a transition towards a more sustainable business, used CSR as a pure strategy to improve the company's image among their clients and potential investors (PwC, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the data stems from its being necessary and from its contribution in supporting management in general, as the management of companies needs extensive, appropriate and timely data for its operations around the world. This data can also contribute to making appropriate adjustments to business plans so that companies are able to know the surrounding environment and improve the process of responding to it proactively (Landi et al, 2022). Furthermore, this data leads to developing more accurate and realistic estimates for management and allows it to obtain more accurate information to deal with the results to meet or to exceed the desire of customers in the markets naturally (Zumente & Bistrova, 2021).…”
Section: Definition Of the Environmental Social And Governance Strate...mentioning
confidence: 99%
“…To thrive in this competitive and global economy, a firm must design an optimal leverage structure that generates a positive change in firm value. The leverage structure affects the cost of financing, thereby impacting the stock's market price (Landi et al, 2022). The comprehensive relationship between leverage structure and firm value has been recognized, but the relationship may vary in signs and traits depending on the development of financial system and corporate governance practices in a country (Uddin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%